Pharmacognostical Studies and Pharmacological Investigations for Anti-diabetic Activities of Taraxacum officinale Weber (Dandelion): Exploring the Anti-diabetic Properties of Taraxacum officinale (Dandelion) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Taraxacum officinale (dandelion) contains active pharmaceutical agents with variousmedicinal activities. This research work was an attempt to establish scientific protocols to performpharmacological investigation research on Taraxacum officinale for antidiabetic effect against STZinduced diabetes in rats. Plant parts were analysed pharmacognostically and authenticated showed thepresence of resin, glycosides, phenolic compounds, flavanoids, steroids, and amino acids. High totalphenolic content and total flavonoid content were found in the EETOL extract then EETOR extract. Invivopharmacological investigation for anti-diabetic activity of EETOL EETOR against streptozotocininduced diabetes was performed and it was found that both EETOL-B extract and EETOL-A extractsproduced significant anti-diabetic effects. EETOL-B extract lowered the blood glucose level, LDL andVLDL significantly and produced better action than EETOL-A. Anti-diabetic potential was comparablewith glipizide (Standard drug). Extract EETOL-B repaired beta cells, revitalized damaged cells, extractsrejuvenates cells and induce insulin secretion. Finally, much more elaborated pharmacological researchis recommended.